Performance and competence in second language acquisition (Cambridge University Press, 1996)
This original collection revisits and re-evaluates Chomsky's classic competence/performance distinction from a wide variety of perspectives and areas of expertise. The discussion is placed within a broad framework, taking account of a view of language both as a societal construct and as internal, developing within the mind and/or brain. Renowned experts in the fields of lexis, sociolinguistics, connectionism, Universal Grammar, language testing and interlanguage draw together ideas from the most recent developments in second language learning and psychological theory